The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1097/00003246-199504000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on bleeding time and clotting time in normal male and female volunteers

Abstract: Our data indicate that during surgical procedures, it is important to maintain normothermia to ensure that platelets and clotting proteins function optimally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 22 publications
7
133
0
6
Order By: Relevance
“…Although studies have been widely conducted, the bleeding time test does not strictly correlate with surgical bleeding. 41,43 Nonetheless, with standardized techniques and knowledge of the merits and limitations of the bleeding time test, it is useful for diagnosing hemostasis disorders, guiding their therapy and warning of unexpected bleeding complications in surgical patients. 44 Stensrud et al 45 evaluated the effects of intraoperative hypothermia on blood transfusion during cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have been widely conducted, the bleeding time test does not strictly correlate with surgical bleeding. 41,43 Nonetheless, with standardized techniques and knowledge of the merits and limitations of the bleeding time test, it is useful for diagnosing hemostasis disorders, guiding their therapy and warning of unexpected bleeding complications in surgical patients. 44 Stensrud et al 45 evaluated the effects of intraoperative hypothermia on blood transfusion during cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia and acidosis are common complications in severely injured patients [1,2]. The negative impact of these conditions on coagulation resulting in coagulopathy has been well described [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia and acidosis are common complications in severely injured patients [1,2]. The negative impact of these conditions on coagulation resulting in coagulopathy has been well described [3][4][5][6][7][8][9].Desmopressin is a synthetic analogue of vasopressin (1-deamino-8-D-aginine vasopressin, DDAVP). Beside its first indication for treatment of cranial diabetes insipidus, it has become the treatment of choice for von Willebrand disease (Type I) and mild haemophilia A after it was shown that DDAVP leads to increased levels of coagulation factor (F) VIII, von Willebrand factor (vWF), and tissue plasminogen activator [10].…”
mentioning
confidence: 99%
“…[1][2][3] Our laboratory also has used the baboon to study the effects of hypothermia on hemostasis before we conducted the experiments in normal volunteers and patients. [4][5][6][7][8][9][10] We have found that data obtained from baboon studies are similar to those seen in studies of normal volunteers and believe that human studies can be reduced by using the baboon in specific areas of research. The following experiments were performed to evaluate the effects of various disinfection treatments on the survival and function of red blood cells and platelets.…”
Section: The Effect Of Disinfection On Viability and Functionmentioning
confidence: 90%